ความสัมพันธ์ระหว่างการรู้ซึ้งถึงความรู้สึกกับความเหนื่อยหน่าย โดยมีแรงงานทางอารมณ์เป็นตัวแปรส่งผ่าน - ณัฐพร ปานเกิดผล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purpose of this research study was to explore the mediating role of emotional labor in the relationship between empathy and burnout. Data were collected by an online survey from 185 healthcare service providers in a hospital, Bangkok Thailand. The results showed that the effects of empathy on each of the three dimensions of burnout (emotional exhaustion, depersonalization, personal accomplishment) were significantly mediated by surface acting. These findings indicated that employees who lacked empathy and engaged with surface acting were likely to experience emotional dissonance from trying to modify their behaviors without shaping their inner feeling which leaded to burnout. While deep acting was a significant mediator in the relationship between empathy and the two dimensions of burnout (depersonalization, personal accomplishment). The findings indicated that employees who engaged with empathy and deep acting were less likely to experience burnout when modify their feelings to match the required behaviors by understanding how customer are feeling so they can respond appropriately to the situation.